Usefulness of determination of CA125 concentration as a marker for ovarian tumours with special consideration of ovarian endometriotic cysts - Wójcik-Krowiranda, Katarzyna; Litwińska, Magdalena; Bieńkiewicz, Andrzej (Menopause Review/Przegląd Menopauzalny, 2010)
Background : CA125 is a mucin-derived glycoprotein. It occurs and is marked mostly among the patients with an ovarian tumour. Nowadays, CA125 antigen is considered to be the best biochemical marker for non-mucinous ovarian cancers. It is also detected in pelvic inflammatory disease, endometriosis, myoma, during menstruation and the 1st trimester of pregnancy. Elevated concentrations of this marker have been also described during non-gynaecological conditions such as hepatocirrhosis and liver cancer, pancreatic, lung, stomach cancers, as well as in lymphoma. Objectives : The aim of the study was to evaluate diagnostic accuracy of CA125 concentration as a marker for ovarian tumours with special consideration of ovarian endometriotic cysts . Material and methods : A total of 124 women with ovarian tumours were included in the study. Patients were divided into three groups: 1. with malignant neoplasm of epithelial origin (n = 30); 2. with ovarian endometriotic cysts (n = 31); 3. with benign ovarian tumours other than endometriotic (n = 63). Prior to planned surgery, CA125 serum level has been estimated in each case. Results : There were statistically significant differences in mean concentration of CA125 between patients with an ovarian cancer and patients with benign ovarian tumours other than endometriotic (p < 0.001). Similarly, statistically significant differences occurred between patients with ovarian endometriotic cysts and patients with non-endometriotic, benign ovarian tumours (p < 0.001). A statistically significant difference has been also observed between patients with endometriotic cysts and patients with an ovarian cancer. Conclusions : 1. Elevated CA125 levels were observed in epithelial neoplasms and also in endometriotic tumours. 2. Elevated CA125 levels were not observed in non-endometriotic benign ovarian tumours. 3. Low CA125 concentrations can occur in both endometriotic cysts and epithelial malignant ovarian tumours.